T-Cell Traffic Jam in Hodgkin's Lymphoma: Pathogenetic and Therapeutic Implications - Claudio Fozza; Maurizio Longinotti (Advances in Hematology)
In hematologic malignancies, the microenvironment is often characterized by nonneoplastic cells with peculiar phenotypic and functional features. This is particularly true in Hodgkin's lymphoma (HL), in which T lymphocytes surrounding Hodgkin's Reed-Sternberg cells are essentially polarized towards a memory T-helper type 2 phenotype. In this paper we will first evaluate the main processes modulating T-cell recruitment towards the lymph node microenvironment in HL, especially focusing on the role played by cytokines. We will then consider the most relevant mechanisms of immune escape exerted by neoplastic cells in order to evade antitumor immunity. The potential pathogenetic and prognostic impact of regulatory T cells in such a context will be also described. We will finally overview some of the strategies of cellular immunotherapy applied in patients with HL.